Elaboración de un plan de mejora en el área de producción de protectores semicirculares de la empresa Servipaxa S.A mediante el análisis de Mudas - Gómez Juma, Marco Andrés (2021)
In the present investigation, the “DEVELOPMENT OF AN IMPROVEMENT PLAN IN THE PRODUCTION AREA OF SEMICIRCULAR PROTECTORS OF THE COMPANY SERVIPAXA S.A THROUGH THE ANALYSIS OF WASTE”, describing the current situation in which the process is, noting that there is no study of work methods and time. With the identification of the doffs, overproduction and overstock are generated by the delayed response to solutions for the machines by the senior administrative officers, generating an excess production due to the distrust that exists in the machines where defective products originate from The same, the waits are created by the bad study of the work where the machine works and the work personnel do not, having percentages of 77% and 83% of idleness, these being the highest, the large number of transports that are had in the process is the inadequate use of the space that you have. In the improvement plan, a redistribution of the plant was elaborated which does not affect other production lines, allowing the elimination of transports, reducing time and space, going from traveling 74.3 meters in 9.02 minutes to obtaining 53.55 meters in 6.6 minutes, generating a reduction of meters of 27.93% and of time of 26.83%, two workers moved from process one to process two in order to eliminate the high percentage of idleness they had, counting on these workers in the preparation of cutting semicircular protectors, stoppages are reduced and production would increase by 85.19%, going from making 135 covers to making 250 covers, where $ 146.16 is reduced from the production cost, which is a saving of $ 2192.40 per month, increasing productivity by 4.62% in the production of semicircular protectors . Keywords: Mutes, Production, Standardization, Optimization.